The institute of head of the state in the mechanism of strengthening state unity and the rule of law (theoretical-historical and constitutional-legal interpretation) - A. V. Bezrukov; V. V. Chugaev (Правоприменение, 2018)
The subject. The article investigates historical legal, theoretical-methodological and constitutional-legal problems of the formation and functioning of the institute of the head of state.The purpose of the study is to show how the constitutional functions of the head of state concretize his powers.The study is based on the use of methods of analysis and synthesis, historical legal, formal legal, comparative legal methods, scientific abstraction.The main scientific results. The authors summarize that the historical and legal analysis shows the key role of the head of state in the mechanism of ensuring state unity and law and order. Reality testifies the fact that the role of the President of the Russian Federation creates sufficient constitutional and legal grounds and conditions for the consolidated work of all state authorities, including law enforcement agencies, in the direction of ensuring the unity of state power and constitutional law and order. The indicated directions are in many ways identical, organically interrelated and interdependent, systematically define the main lines of activity of the head of state, contributing to the improvement of the constitutional and legal mechanism for ensuring the rule of law in general. Firstly, the Constitution of the Russian Federation contains only the basic powers of the President of the Russian Federation, which are substantially expanded by the legislator and presidential decrees. Secondly, the President has so-called “hidden”, discretionary powers that are not directly enshrined in the Constitution of the Russian Federation, implicit in it and stem from the sense of presidential functions that manifest themselves in unforeseen extraordinary circumstances. Thus, the constitutional design of a strong presidential power allows the President of the Russian Federation to ensure the unity of the executive power and the exercise of the powers of the federal government throughout the territory of Russia (pt. 4 of Art. 78 of the Constitution of the Russian Federation). Such presidential power is carried out through the issuance of its decrees and orders, the adoption of operational and administrative decisions.Conclusions. The authors noted that the effectiveness of the work of the head of state is especially evident in the state unity and the constitutional and legal mechanism for ensuring the rule of law, which is developed in the constitutional doctrine.